Short- and long-term effects on reproductive parameters of female Wistar rats after exposure to rosuvastatin starting in pre-puberty - Barros, Jorge W.F.; Tonon, Karolina S. [UNESP]; Borges, Cibele S. [UNESP]; Silva, Patrícia V. [UNESP]; Lozano, Ana F.Q.; Pacheco, Tainá L.; Anselmo-Franci, Janete A.; Kempinas, Wilma G. [UNESP] (Elsevier, 2020)
Statins are a class of drugs that act lowering lipid levels by inhibiting cholesterol biosynthesis. Additionally, statins can act by “pleiotropic effects”, related to the inhibition of synthesis of the other mevalonate pathway products. Rosuvastatin is a third-generation statin and has shown better results in reducing cholesterol concentrations when compared to other statins. Recent studies suggest that rosuvastatin may act as an endocrine disruptor that potentially damages the hormonal axis and, consequently reproductive development and function of male rats. However, the effects of rosuvastatin exposure on rat female reproductive parameters remain unknown. In this study female rats were exposed to rosuvastatin at the doses of 0 (control), 3, or 10 mg/Kg.bw−1/day from pre-puberty to adulthood. No alterations in the female reproductive parameters were observed at a dose of 3 mg/Kg.bw−1. However, females exposed to 10 mg/Kg.bw−1 exhibited shorter estrous cycles, altered copulatory behavior, decreased serum prolactin level, and alterations in the liver, pituitary and placental weights, parameters to some extent influenced by the reproductive hormonal axis signaling pathway. On the other hand, pubertal onset, reproductive hormone levels, fertility, and histological parameters of the ovary, uterus, and placenta were unaltered by exposure to both doses of this statin. Thus, rosuvastatin exposure, at the higher dose, altered the reproductive function of female rats, probably due to the pleiotropic effects of this statin. Additional studies on the effects of this statin on female reproductive function and development are encouraged to better characterize its mode of action.
Keywords: Pleiotropic effects; Rat female reproduction; Rosuvastatin; Statin